E-Government - an information security perspective - Hassan, Rasha G.; Khalifa, Othman Omran (International Journal of Computer Trends and Technology, 2016)
The growth and rapid adoption of the Internet has greatly changed how all organizations deal with their respective stakeholders. As the move from administrative operations to service operations accelerates, e- government Network Platform is a solution to transform the way they do business and services. As well know, the E-government is a website that provides reliable content based on a strong infrastructure of a digital network, application servers and internet, an extensive database and other supporting services. It requires more advanced and secure e-Government networks to protect data from growing security threats and risks. Threats include unauthorized access to resources, malicious damage, and data intercepts. Security risks include virus, cyber-attacks, and key information leakages. Experts agree that the majority of government information leaks occur on networks, making information leakage control critical in government network design.